2020
DOI: 10.3390/jcm9092748
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sense of Voice Presence and Anxiety Reduction in AVATAR Therapy

Abstract: AVATAR therapy offers a unique therapeutic context that uses virtual reality technology to create a virtual embodiment of the voice-hearing experience, enabling the person to visualize their persecutory voice and engage in real-time “face-to-face” dialogue. The present study explores, for the first time, the contribution of sense of voice presence, together with session-by-session reduction of anxiety and paranoid attributions about the avatar, to changes in primary outcomes following AVATAR therapy. Data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 44 publications
1
31
0
1
Order By: Relevance
“…Clearly a crucial question is whether the influence of voice characterisation on engagement in AVATAR dialogue leads to improvement in the actual distressing voices. Rus-Calafell et al (2020) have demonstrated that the interaction between sense of voice presence (i.e. virtual embodiment of the 'voice as avatar') and reduction of anxiety predicted improvement in two of the Psychological Medicine 5 significant AVATAR therapy outcomes: PSYRATS (Haddock, McCarron, Tarrier, & Faragher, 1999) total and frequency of voices.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly a crucial question is whether the influence of voice characterisation on engagement in AVATAR dialogue leads to improvement in the actual distressing voices. Rus-Calafell et al (2020) have demonstrated that the interaction between sense of voice presence (i.e. virtual embodiment of the 'voice as avatar') and reduction of anxiety predicted improvement in two of the Psychological Medicine 5 significant AVATAR therapy outcomes: PSYRATS (Haddock, McCarron, Tarrier, & Faragher, 1999) total and frequency of voices.…”
Section: Discussionmentioning
confidence: 99%
“…Distressing voices are typically characterized by negative content and affective consequences (Beavan & Read, 2010; Close & Garety, 1998; Nayani & David, 1996). AVATAR therapy provides a realistic simulation of the persecutor’s voice heard by the person during everyday life, which seems to be crucial to important therapy outcomes (Rus‐Calafell et al., 2020). Although direct use of abusive verbatim voice content presents challenges, accurately representing voice content provides an opportunity for validation of experiences and may facilitate habituation (Rus‐Calafell et al., 2020; Ward et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of AVATAR Therapy in this recent trial resulted in an evolution in our understanding of the core therapy processes and how these might, in principle, differ between a standardised phase 1 focusing on exposure and assertiveness, and a formulation-driven phase 2 incorporating a broader range of treatment targets [ 14 ]. Data from the previous trial suggest that anxiety reduction is especially prominent during phase 1, but that other processes during phase 2, including changes in the perceived omnipotence and malevolence of the voice, may contribute to improved treatment outcomes, at least for some participants [ 17 ]. The new trial develops these insights and aims to make progress towards increased availability of AVATAR therapy in routine mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, AVATAR therapy as delivered in the previous trial comprises two phases. The trial therapists noted that phase 1 in itself was a powerful intervention for a sizeable number of people, which was supported by evidence within the AVATAR therapy arm of significant anxiety reduction during sessions 1–3 [ 17 ]. On the other hand, for some people, anxiety reduction alone may be insufficient to produce optimally effective lasting change, and therefore an approach including both phases may be necessary (see the ‘ Introduction ’ section).…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation